The severity assessment of critically ill preeclamptic women: a case-control study - João Paulo Souza; Geraldo Duarte; Aníbal Basile-Filho (2006)
The assessment of illness severity and prognosis of obstetric patients by scoring systems is still a controversial issue. Preeclampsia is a leading cause of severe maternal morbidity and mortality, and a major cause of obstetric admission to intensive care unit. There is paucity of data regarding the predictability of critically ill preeclamptic women and the application of scoring systems to this population. This study aimed to evaluate and compare the application of APACHE II, SAPS II and MPM II scoring systems between a preeclamptic population and a non obstetric female population.A case-control study was conducted on 28 preeclamptic women and 56 non obstetric female patients, admitted to a general intensive care unit over a period of 10 years. The predictive accuracy of the prognostic evaluation systems was estimated by the area under the receiver operator characteristic curve.The mortality rate was 21.4% (6:28) for the study group and 35.7% (20:56) for the control group, with an OR = 0.49 (95%CI = 0.17-1.41). The main causes of ICU admission of preeclamptic women were HELLP syndrome, coma and pulmonary edema. In the preeclamptic population, only the MPM II score showed an area under the ROC curve statistically different from 0.500, while in the control group, all scoring systems had their areas under the ROC curves statistically different from 0.500.The application of APACHE II and SAPS II to evaluate critically ill preeclamptic women may be not appropriate.